Determinan Kinerja Petugas Rumah Sakit Klaim Badan Penyelenggara Jaminan Kesehatan - Ismawati, Nidiya; Sudiyanto, Henry; Anggreni, Dhonna (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2025)
The performance of officers in BPJS Kesehatan claims plays a crucial role in ensuring the smooth administration of services in hospitals. The high number of pending claims reflects problems with individual abilities, support systems, and internal hospital management. This study aims to analyze the influence of ability, motivation, and opportunity factors on the performance of BPJS Kesehatan claims officers at Kamar Medika Hospital, Mojokerto. This study employs a cross-sectional, observational, and analytical method. The study population is all officers involved in the BPJS Kesehatan claims process. A sample of 56 respondents was selected using a simple random sampling technique. The data instrument was a questionnaire, which was then analyzed using the Chi-Square test and Logistic Regression. The results showed that most respondents had a high level of ability (58.9%), high motivation (64.3%), high opportunity (67.9%), and high performance (67.9%). The results of the Chi-Square test showed that ability (p-value = 0.036), motivation (p-value = 0.033), and opportunity (p-value = 0.010) significantly influenced the performance of officers in BPJS Kesehatan claims. Multivariate testing revealed that ability had a significant influence on officer performance (p-value = 0.042). The ability factor significantly influenced employee performance in BPJS Health claims at Kamar Medika Hospital, Mojokerto